Do we really need nutraceutical liver support? Experimental effectiveness, risks and proven clinical benefits - Francesco Marotta; Aldo Lorenzetti; Saida Rasulova; Baskar Balakrishnan; Anna Cabeca; Fang HE (Open Journal of Hepatology - Peertechz Publications, 2021)
Liver is the largest and one of the most metabolically active organ in the body. With a crucial role in the clearance of toxins such as aflatoxins, microbes and metabolic by-products. This constant exposure to inner and environmental harmful substances may be potentially overwhelmed and be affected by a degree of liver damage ranging from hepatitis and Non-Alcoholic Fatty Liver Disease (NAFLD), Non-Alcohol Steatohepatitis (NASH), These latter two with worrying worldwide expansion (Figure 1) up to liver cirrhosis and hepatocellular carcinoma while representing a risk factor for other illnesss such as cardiovascular disease, stroke and diabetes.